2004
DOI: 10.1021/jo035835h
|View full text |Cite
|
Sign up to set email alerts
|

Fused-Ring Thiadiazines:  Preparation and Crystallographic Characterization of 3-Phenyl Derivative of Benzo-, Pyridio[2,3-e]-, Pyrazino[2,3-e]-, and Tetrafluorobenzo-[1,2,4]thiadiazines

Abstract: Four bicyclic 4H-[1,2,4]thiadiazines 1a-d were prepared in 74-88% yields in two steps from the corresponding amidines 2. Three of them, 1a, 1b, and 1d, were obtained by thermal elimination of propene from the intermediate S-propylsulfilimines 12. The pyrazino derivative 1c was formed upon thermolysis of sulfoxide 14c obtained from 2c. The E(i) mechanism was investigated using DFT methods. The elimination in the sulfilimine appears to be more favorable by about 2 kcal/mol than in the analogous sulfoxide. Crysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 48 publications
0
21
0
3
Order By: Relevance
“…Treatment of 2-chloronitrobenzene with 1.0 equiv of sodium thiomethoxide in DMSO at 90 8C afforded 2-methylthionitrobenzene 1a. Reaction of 2-chloronitrobenzene with 1.1 equiv of 2-propanethiol and NaOH in EtOH at room temperature afforded 2-isopropylthionitrobenzene 1b, [16] followed by reduction of zinc dust in the presence of glacial acetic acid to generate the corresponding anilines 2.…”
Section: Synthesis and Characterization Of Ti Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment of 2-chloronitrobenzene with 1.0 equiv of sodium thiomethoxide in DMSO at 90 8C afforded 2-methylthionitrobenzene 1a. Reaction of 2-chloronitrobenzene with 1.1 equiv of 2-propanethiol and NaOH in EtOH at room temperature afforded 2-isopropylthionitrobenzene 1b, [16] followed by reduction of zinc dust in the presence of glacial acetic acid to generate the corresponding anilines 2.…”
Section: Synthesis and Characterization Of Ti Complexesmentioning
confidence: 99%
“…Deuterated solvents were dried using standard procedures and stored in the glovebox. Compounds 1b, [16] 2a-b, [13c] and 4c [13b,13c] (Scheme 1) were prepared according to literature methods. Other chemicals were used as received unless otherwise noted.…”
mentioning
confidence: 99%
“…Amidines were used as important synthon in organic synthesis in the preparation of various heterocyclic compounds, such as pyridine [7, 9], pyrimidines [9, 10], imidazoles [11], pyrazolopyrimidine [12], iminopyrimidine [13], imidazopyridine and pyrimidinopyridine [14], purine [15], benzimidazole [16], pyrimidines [17], triazaphenalene [18], triazine [19], tetraazole [19], thiadiazine [20], oxazolotriazole [21], diazirine [22], triazolopyridine [23], azetidinone [24], and pyrrole, and also used as complexing agent [25]. …”
Section: Introductionmentioning
confidence: 99%
“…Generally, nitriles were activated to the intermediate salt in the presence of EtOH/HCl [26] or NH 4 Cl/MeOH [27] under anhydrous condition and then reacted with amine to get amidine. While for unreactive nitriles, Lewis acid or other condensing agents were used such as anhydrous AlCl 3 , ZnCl 2 [28], CuCl [29], Ln (III) salts [30], CaCl 2 [31], Al(CH 3 ) 3 [32], SmI 2 [33], Ytterbium amide [34], MeSO 3 H [20], and anhyd. SnCl 4 [21].…”
Section: Introductionmentioning
confidence: 99%
“…10 Synthesis of heterocycles containing sulfur and nitrogen heteroatoms has shed still more light in heterocyclic chemistry. [11][12][13] Rees reported that 4-dicyanomethylene-1,2,6-thiadiazine was obtained from the reaction of tetracyanoethylene with SCl 2 . 14 In literature, four classes of TCNE-derivative heterocycles can be identified: (i) reaction products obtained by nucleophilic attack on tetracyanocyclopropenes which, in turn, are formed from the reaction of TCNE with aliphatic monobromides; (ii) products resulting from interconversion of unstable charge-transfer compounds of TCNE and an electron-donor; (iii) Diels-Alder cycloadducts between TCNE and a diene; and (iv) products derived from previously unknown reactions of TCNE.…”
mentioning
confidence: 99%